A method for making a perovskite solar cell

By modifying commercial SAMs materials to form hydrophilic SAMs complex modifiers, it is used in the nickel oxide hole transport layer of perovskite solar cells, solving the problem of increasing open circuit voltage and short-circuit current, and improving perovskite batteries conversion efficiency.

CN118765146BActive Publication Date: 2024-12-24杭州柯能新能源有限公司 +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411237653.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-05
Publication Date
2024-12-24
Estimated Expiration
2044-09-05

AI Technical Summary

Technical Problem

When using nickel oxide as the hole transport layer material for existing perovskite solar cells, the open circuit voltage is insufficient and the short circuit current is reduced, making it difficult to improve both at the same time to improve the conversion efficiency.

Method used

The commercial SAMs material was modified by using Lewis alkaline molecule DP, and a SAMs complex (DP-SAM-1) modified agent was formed by solution method to modify the nickel oxide holes of perovskite solar cells. Transport layer, alternative to commercial SAMs materials.

Benefits of technology

It effectively reduces surface defects, improves open circuit voltage and short circuit current, and enhances the energy conversion efficiency of perovskite batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118765146B_ABST
    Figure CN118765146B_ABST
Patent Text Reader

Abstract

The present application provides a method for making a perovskite solar cell. The method uses a commercial self-assembling molecule (SAMs) material (i.e., a SAMs complex modifier DP-SAM-1) modified by a Lewis base molecule (phthalimidomethyl) diethyl phosphate (DP) to treat the surface of the nickel oxide hole transport layer of the perovskite solar cell to improve the open circuit voltage loss. The modified commercial self-assembling molecule (SAMs) material is used to replace the commercial self-assembling molecule (SAMs) with strong hydrophobicity and uncontrolled self-assembly state on the surface of the nickel oxide hole transport layer to modify the nickel oxide hole transport layer. Compared with the use of commercial self-assembling molecules (SAMs) alone to modify the nickel oxide hole transport layer, the modified commercial self-assembling molecule (SAMs) material effectively improves the surface wettability of the perovskite precursor solution, makes the surface of the nickel oxide hole transport layer more uniform in molecular size, and improves the open circuit voltage, short circuit current and energy conversion efficiency of the perovskite solar cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of optimization / improvement of manufacturing process of solar cells, and in particular to a method for manufacturing perovskite solar cells. Background Art

[0002] As an important direction for the development of new energy, solar cells have reduced their unit power generation cost to a level close to that of thermal power with the development of technology and the maturity of manufacturing processes. Perovskite solar cells have attracted much attention in the industry for their high power generation efficiency and low material acquisition cost, and have become an important branch of solar cell development.

[0003] Currently, the mainstream inverted (pin) perovskite solar cells (PSCs) use nickel oxide (NiO X ) is used as a material for preparing the hole transport layer because it is easier to obtain and cheaper than other hole transport materials. However, there is also an obvious disadvantage of using nickel oxide to make the hole transport layer. The open circuit voltage of the perovskite solar cell made in this way is insufficient. Commercial self-assembled molecules (SAMs) are usually used as surface modifiers to treat NiO X However, due to the strong hydrophobicity of SAMs materials, when treating NiO X The surface is prone to poor interface morphology and high defect density, which in turn leads to a decrease in the short-circuit current of the manufactured perovskite solar cell. X On the surface, it is difficult to simultaneously increase the open-circuit voltage and short-circuit current, which limits the improvement of the conversion efficiency of perovskite solar cells. Summary of the invention

[0004] In order to improve the open circuit voltage of a perovskite solar cell while improving or at least not reducing its short circuit current, the present invention provides a method for making a perovskite solar cell. The method uses a Lewis base molecule (phthalimidomethyl) diethyl phosphate (DP) to modify commercial SAMs materials (Me-4PACz, MeO-2PACz, Me-PhpPACz, etc.), and a SAMs complex modifier (DP-SAM-1) formed by a solution method replaces the SAMs material as a surface modifier of the nickel oxide hole transport layer of the perovskite cell, and performs interface treatment on the nickel oxide hole transport layer of the perovskite solar cell. The SAMs complex modifier has good hydrophilicity, and when used for surface modification of the nickel oxide hole transport layer of the perovskite solar cell, it can reduce defects and form an interface with a better morphology, and can simultaneously enhance the open circuit voltage and short circuit current of the perovskite cell, thereby improving its energy conversion efficiency.

[0005] The method for making a perovskite solar cell provided in the present application comprises: spin coating nickel oxide (NiO X ), and annealing to prepare the nickel oxide hole transport layer; a layer of modifier is spin-coated on the prepared nickel oxide hole transport layer as a buffer layer, wherein the modifier is a Lewis base small molecule DP containing a phosphorus oxygen bond (-P=O) and a carbon oxygen double bond (-C=O) and a SAMs material, and a SAMs complex modifier (DP-SAM-1) synthesized by a solution method. The SAMs material includes at least one of Me-4PACz, MeO-2PACz and Me-PhpPACz. After the buffer layer is prepared, a perovskite film layer is prepared by spin-coating a perovskite precursor solution.

[0006] Furthermore, the method further comprises performing the following cleaning treatment on the FTO conductive glass: spin coating nickel oxide (NiO X ), the FTO conductive glass was continuously ultrasonically washed in ethanol, deionized water, acetone, ethanol and isopropanol for 15 min, then dried under nitrogen conditions and treated with UV / ozone for 20 to 30 min.

[0007] Furthermore, the SAMs complex modifier is prepared by dissolving a Lewis base small molecule DP solvent with a concentration of 1 mg / mL and a SAMs material Me-4PACz solvent with a concentration of 1 mg / mL in isopropanol, and oscillating the reaction for 20 minutes under nitrogen protection.

[0008] Furthermore, the perovskite molecular structure in the perovskite precursor solution is ABX3, which is obtained by dissolving Pb salt and formamidine iodide or cesium salt in an organic solvent in any proportion; wherein A is one or more of FA+, MA+, Cs+, B is one or more of Pb2+, Sn2+, and X is one or more of Cl-, Br-, I-.

[0009] Furthermore, the method further comprises: preparing an electron transport layer by spin coating an electron transport layer material on the heated and annealed perovskite thin film layer, and vacuum depositing a metal electrode on the electron transport layer.

[0010] Preferably, the electron transport layer material is a PC61BM [6,6]-phenyl C61 butyric acid methyl ester solution with a purity of >99%. The electron transport material is prepared by weighing a sufficient amount of PC61BM and dissolving it in a certain volume of chlorobenzene, heating it at 40°C with a magnetic pole, and stirring it for 1 hour.

[0011] The present invention uses small molecule Lewis base DP molecules to modify commercial SAMs materials and obtains a hydrophilic SAMs complex (DP-SAM-1) modifier through liquid phase reaction. The SAMs complex modifier is used to modify the surface of the nickel oxide hole transport layer of the perovskite solar cell, so that the wettability of the nickel oxide substrate surface to the perovskite precursor solution is greatly improved, and the surface defects are greatly reduced; the open circuit voltage and short circuit current of the device are simultaneously improved.

[0012] Reduce the occurrence of non-radiative recombination and improve the energy conversion efficiency of the device. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 A flow chart of a method for manufacturing a perovskite cell provided by the present invention in one embodiment.

[0014] Figure 2a NiO modified with DP-SAM-1 and treated with commercial SAMs only X XPS spectrum of the substrate.

[0015] Figure 2b DP-SAM-1 modified and the original material (NiO X FTIR spectrum of substrate).

[0016] Figure 3a , 3b NiO X Contact angle test results of the perovskite precursor solution with the hole transport layer treated only with commercial SAMs materials and modified with DP-SAM-1.

[0017] Figure 4a , 4b NiO X SEM photos of the hole transport layer treated only with commercial SAMs materials and the perovskite buried layer modified with DP-SAM-1. DETAILED DESCRIPTION

[0018] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Generally, the components of the embodiments of the present invention described and shown in the accompanying drawings here can be arranged and designed in various different configurations.

[0019] The present invention provides a method for manufacturing a perovskite solar cell based on a SAMs complex (DP-SAM-1) modifier prepared by liquid phase reaction by modifying a commercial SAMs material with a small molecule Lewis base DP molecule. The complex modifier has good hydrophilicity and can be used to modify the surface of the nickel oxide hole transport layer to effectively reduce defects, improve the open circuit voltage and short circuit current of the perovskite cell, reduce the non-radiative recombination of carriers, and improve the energy conversion efficiency.

[0020] like Figure 1 In the embodiment shown, the method for manufacturing a perovskite solar cell provided by the present invention comprises the following steps:

[0021] S10, the FTO conductive glass is cleaned as follows. This step mainly uses various detergents to clean the FTO conductive glass as a substrate to avoid affecting the performance of the subsequent perovskite solar cell.

[0022] Preferably, this step can be achieved by spin coating nickel oxide (NiO X ), the FTO conductive glass was continuously ultrasonically washed in ethanol, deionized water, acetone, ethanol and isopropanol for 15 min, then dried under nitrogen conditions and treated with UV / ozone for 20 to 30 min.

[0023] S11. Prepare the nickel oxide hole transport layer of the perovskite cell on the FTO substrate. This step can be achieved by filtering a certain amount of nickel oxide in deionized water with polytetrafluoroethylene, and then coating it on the FTO substrate to prepare the hole transport layer. For example, weigh 20 mg of nickel oxide, disperse it in deionized water, filter it with 22 um polytetrafluoroethylene, spin-coat it on the FTO substrate at 1500 rpm / min for 30 seconds, anneal it at 150°C for 10 minutes, and then immediately transfer it to the glove box.

[0024] S12. Commercial SAMs materials were modified based on Lewis base small molecules DP containing phosphorus oxygen bonds (-P=O) and carbon oxygen double bonds (-C=O) to prepare SAMs complex (DP-SAM-1) modifiers. For example, DP (1 mg / ml) and Me-4PACz were dissolved in isopropanol, and the SAMs complex (DP-SAM-1) modifier was formed by shaking reaction for 20 min under nitrogen protection, and stored in a brown bottle to avoid photodegradation.

[0025] Obviously, the commercial SAMs material used in the preparation of the SAMs complex (DP-SAM-1) modifier is not limited to Me-4PACz, and other SAM materials are also possible. The SAMs material includes at least one of Me-4PACz, MeO-2PACz and Me-PhpPACz.

[0026] S13, spin coating the SAMs complex (DP-SAM-1) modifier on the nickel oxide hole transport layer to form a buffer layer. For example, spin coating on the NiOx nickel oxide hole transport layer at a rotation speed of 5000 rpm / min for 30 seconds.

[0027] S14, spin coating the perovskite precursor solution on the prepared buffer layer to prepare a perovskite thin film layer. Preferably, the perovskite molecular structure in the perovskite precursor solution is ABX3, which is obtained by dissolving Pb salt and formamidine iodide or cesium salt in an organic solvent in any proportion; wherein A is one or more of FA+, MA+, and Cs+, B is one or more of Pb2+ and Sn2+, and X is one or more of Cl-, Br-, and I-.

[0028] In one embodiment, the perovskite precursor solution can be prepared in the following manner: weigh 228.4 mg FAI, 18.2 mg CsI and 645.4 mg PbI2, dissolve them in 800 ul DMF and 200 ul DMSO, oscillate and weld for 6-8 hours at 1000 rpm / min for 10 s, then at 4000 rpm / min for 40 s, quickly and evenly add 150 ul CB anti-solvent at 42 s, and anneal at 100°C for 30 minutes.

[0029] S15, preparing an electron transport layer on the perovskite thin film layer. After heating and annealing, the electron transport layer of the perovskite solar cell is prepared by spin coating the electron transport layer material.

[0030] Preferably, the electron transport layer material is a PC61BM [6,6]-phenyl C61 butyric acid methyl ester solution with a purity of >99%. The electron transport material is prepared by weighing a sufficient amount of PC61BM and dissolving it in a certain volume of chlorobenzene, heating it at 40°C with a magnetic pole, and stirring it for 1 hour.

[0031] S16, vacuum depositing a metal electrode on the electron transport layer. After the metal electrode is deposited (or the monomer is cut), a battery monomer capable of converting solar energy and outputting electrical energy is formed.

[0032] Compared with the commercial SAMs material modifier alone, the electronegativity of the SAMs complex (DP-SAM-1) modifier used in this application can be judged to be more balanced through molecular electrostatic potential calculation analysis and energy level calculation. The modified layer (buffer layer) prepared by this modifier is similar to NiO X The energy level of the hole transport layer is more matched, which can effectively solve the wettability / hydrophobicity problem in the preparation of perovskite solar cells and improve the hole transport performance.

[0033] Figure 2aX-ray energy spectrum (XPS) test shows that the SAMs complex (DP-SAM-1) modifier and NiO X The substrate has a strong bonding effect, which suppresses oxygen defects and improves the Ni 3+ proportion. Figure 2a These data explain the mechanism by which DP-SAM-1 modifiers enhance hole transport capabilities.

[0034] Figure 2b The XPS Fourier transform infrared (FTIR) test results explain the synthesis principle of the DP-SAM-1 modifier in the solution: the red shift of the phosphorus oxygen bond and the blue shift of the carbon oxygen bond indicate that the two groups have vibrated in the synthesis process, especially the red shift of the carbon oxygen bond shows that it is affected by the steric hindrance of the larger SAMs molecule in the complex. These data prove the effective synthesis of the SAMs complex (DP-SAM-1) modifier and also explain its effectiveness principle.

[0035] like Figure 3a , Figure 3b The contact angle comparison test of the perovskite precursor solution shown in the figure shows that NiO X On the substrate, the perovskite precursor solution has a large contact angle of 39°. The use of the SAMs complex DP-SAM-1 modifier significantly reduced the contact angle of the perovskite precursor solution to 13°, and the wettability was significantly improved. The improvement in wettability is due to the fact that the polar functional group carbonyl (-C=O) in the SAMs complex DP-SAM-1 modifier can form hydrogen bonds with polar solutions and reduce surface energy.

[0036] Figure 4a , Figure 4b The perovskite films on different substrates (using SAMs material alone as a modifier for the nickel oxide hole transport layer, and using the SAMs complex DP-SAM-1) were peeled off with UV glue and scanning electron microscope (SEM) photos of the buried layer were taken. Figure 4a , 4b It can be observed that the buried interface treated only with commercial SAMs molecules shows more micropores in the perovskite, while the buried interface treated with DP-SAM-1 complex modifier completely eliminates the micropores and the morphology becomes uniform and dense.

[0037] The above description is only an embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for manufacturing a perovskite solar cell, characterized in that: The method comprises: spin coating a layer of modifier as a buffer layer on a prepared nickel oxide hole transport layer, and spin coating a perovskite precursor solution on the buffer layer to prepare a perovskite film layer; the modifier is a complex modifier synthesized by a solution method of a Lewis base small molecule diethyl phthalimide methyl phosphonate containing a phosphorus oxygen bond (-P=O) and a carbon oxygen double bond (-C=O) and a self-assembling molecular material; the self-assembling molecular material comprises at least one of Me-4PACz, MeO-2PACz and Me-PhpPACz.

2. The method according to claim 1, characterized in that The method comprises: spin coating nickel oxide (NiO X ) and annealing to prepare the nickel oxide hole transport layer.

3. The method according to claim 2, characterized in that The method further comprises: spin coating nickel oxide (NiO X ), the FTO conductive glass was continuously ultrasonically washed in ethanol, deionized water, acetone, ethanol and isopropanol for 15 min, then dried under nitrogen conditions and treated with UV / ozone for 20 to 30 min.

4. The method according to claim 3, characterized in that The complex modifier is prepared by dissolving a Lewis base small molecule diethyl phthalimide methyl phosphonate solvent with a concentration of 1 mg / mL and a self-assembling molecular material Me-4PACz solvent with a concentration of 1 mg / mL in isopropanol, and oscillating and reacting for 20 minutes under nitrogen protection.

5. The method according to any one of claims 1 to 4, characterized in that The perovskite molecular structure in the perovskite precursor solution is ABX3, which is obtained by dissolving Pb salt and formamidine iodide or cesium salt in an organic solvent in any proportion; wherein A is one or more of FA+, MA+, Cs+, B is one or more of Pb2+, Sn2+, and X is one or more of Cl-, Br-, I-.

6. The method according to claim 5, characterized in that The method further comprises: An electron transport layer is prepared by spin coating an electron transport layer material on the heated annealed perovskite film layer, and a metal electrode is vacuum deposited on the electron transport layer.

7. The method according to claim 6, characterized in that The electron transport layer material is a PC61BM[6,6]-phenyl C61 butyric acid methyl ester solution with a purity of >99%.

8. The method according to claim 7, characterized in that The electron transport material is prepared by the following method: a sufficient amount of PC61BM is weighed and dissolved in a certain volume of chlorobenzene, and the mixture is heated at 40° C. by a magnetic device and stirred for 1 hour.

Citation Information

Patent Citations

  • Composite hole transport layer and preparation method thereof, and inverted perovskite solar cell

    CN118139431A

  • Band edge adjustable perovskite solar cell and preparation method thereof

    CN118368910A